2009
DOI: 10.1159/000210097
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of the Complications of Gastroesophageal Reflux Disease

Abstract: The complications of gastroesophageal reflux disease (GERD) include ulcers, strictures, Barrett’s esophagus and carcinoma. Although the prevalence of GERD is very high, the development of complications remains quite rare and usually occurs in association with factors generally observed in more severe disease such as hiatal hernia, bile reflux or severely disturbed motility. Recent studies have emphasized the role of obesity and genetic factors as aggravating factors in the development of GERD complications. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 88 publications
1
18
0
1
Order By: Relevance
“…Short-term data suggest that POEM is as effective as LHM in treating dysphagia with similar rates of postoperative reflux although randomized controlled trials have yet to be performed [17][18][19]. In cohort studies, postoperative reflux is reported in 0-53 % of patients following POEM [6][7][8][20][21][22]. Some of this variability may relate to differences in subjective and objective measurements of acid reflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term data suggest that POEM is as effective as LHM in treating dysphagia with similar rates of postoperative reflux although randomized controlled trials have yet to be performed [17][18][19]. In cohort studies, postoperative reflux is reported in 0-53 % of patients following POEM [6][7][8][20][21][22]. Some of this variability may relate to differences in subjective and objective measurements of acid reflux.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Heller myotomy, no anti-reflux procedure is included and the rate of postoperative reflux has varied widely from 0 to 53 % in published studies [2][3][4]. This variation has created debate as to whether all patients should be treated with acid suppression postoperatively to avoid the complications of uncontrolled reflux such as erosive esophagitis, peptic stricture, and Barrett's esophagus [5][6][7].An alternative to lifelong treatment with proton pump inhibitors (PPI) is tailored PPI use based on the presence of …”
mentioning
confidence: 99%
“…According to previous studies, tobacco, alcohol, and obesity may be risk factors for GEJA [33,34,35,36,37]. Accordingly, we retrospectively investigated patients in the GEJA group and the distal gastric cancer group to obtain information regarding smoking and drinking history, measured height and weight, and calculated the body mass index (BMI) of patients using medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Efficacy was approximately the same in patients with or without Barrett's esophagus and there was no further aggravation of lesions or malignant degeneration [86]. The role of maintenance PPI therapy in the prevention of complications is also suggested by epidemiological studies showing decreased stricture prevalence during recent decades [87].…”
Section: Long-term Management With Ppi Therapymentioning
confidence: 97%